Effects of non-fasting molting on performance, oxidative stress, intestinal morphology, and liver health of laying hens - Lei, Meng; Shi, Lei; Huang, Chenxuan; Yang, Yawei; Zhang, Bo; Zhang, Jianshe; Chen, Yifan; Wang, Dehe; Hao, Erying; Xuan, Fengling; Chen, Hui (Frontiers in Veterinary Science, 2023)
Animal welfare concerns in laying-hen production facilities have necessitated research on alternative strategies for improving egg production and hen health. Therefore, this study investigated the effects of non-fasting molting on production performance, oxidative stress, intestinal morphology, and liver health of laying hens. A total of 180 healthy 90-week-old Dawu Jinfeng laying hens with similar body weights and laying rates (76±2%) were randomly divided into three groups, with five replicates per group and 12 hens per replicate. The hens in the NF group were molted using the non-fasting method, the C group was not treated with centralized molting, and the F group was molted using the fasting method. The results showed that: 1) During the molting period, the laying rate in the NF group (10.58%) decreased and was significantly lower than that in the other two groups (P < 0.05). During the secondary laying peak period, the laying rate in the NF group was highest (89.71%); significantly higher than that in the C group (P < 0.05). 2)During the molting period, there was no significant difference in MAD and CORT among the three groups, but the contents of MAD and CORT in NF group was lower than that in F group. 3)During the molting period, the villus height (VH) and the ratios of VH to crypt depth (V/C) of the duodenum, jejunum, and ileum in the NF group were significantly lower than those in the C group (P < 0.05). At the secondary laying peak period, the V/C of duodenum, jejunum and jejunum in the NF group were increase. 4) During the molting period, the serum glutathione transaminase (AST) and glutathione alanine transaminase (ALT) were significantly lower in the NF group than in the F group (P < 0.05). Furthermore, there was a low degree of liver injury in the NF group. At the secondary laying peak period, the liver returned to normal. In summary, non-fasting molting can improve the production performance of laying hens in the later stages, ensure the welfare and health of animals, and provide a theoretical basis for the efficient production of laying hens.